Development and Alpha Testing of EzHifz Application: Al-Quran Memorization Tool. (11th May 2021) - Mustafa, Nor Musliza; Mohd Zaki, Zulkifly; Mohamad, Khairul Anuar; Basri, Mokmin; Ariffin, Sedek
Abstract : Learning to memorize the Quran presents a challenge. This paper reports the development and alpha testing of a mobile application called "EzHifz" for Quran memorization based on the VARK learning style. The application received positive feedback for user acceptance testing and heuristic testing. The Fleiss kappa coefficient ( κ ) results for user acceptance testing show a very good level of agreement ( κ  = 0.850). Heuristic testing results show that κ  = 0.731 for content, manual guide, memorization activities, performance information, and tasmik assessment attributes, while κ  = 0.727 for presentation design, interactivity, multimedia elements, attraction, and motivation attributes. These results show a good level of agreement, which indicates that the EzHifz application meets the requirements of design and development based on the attributes evaluated. A combination of memorizing techniques in the application helps strengthen the use of preferred VARK learning styles. The techniques support the use of multiple senses that could facilitate the process of memorizing the Quran independently. This study contributes to the novel design and evaluation of the Quran memorization application based on the Quran memorization model. The application supports the teaching and learning of Quran memorization where it allows students to select their preferred VARK learning style with the technique of memorizing the Quran. This mobile application learning approach based on VARK's learning style has the potential to be implemented in the process of memorizing the Quran as well as retaining memory through the use of memory senses in support of the learning materials developed.